WORK-LIFE BALANCE AND EMPLOYEE PRODUCTIVITY IN INDONESIAN SERVICE SECTOR - Susanto, Bambang; Agusiady, Ricky; Aripin, Zaenal (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background: Work-life balance has become increasingly critical as Indonesian service sector employees face mounting pressures from extended working hours and digital connectivity expectations. Aims: This study investigates the relationship between work-life balance and employee productivity in Indonesian service organizations. Research Method: Survey-based quantitative approach involving 245 employees from banking, telecommunications, and hospitality sectors across Jakarta, Surabaya, and Bandung. Results and Conclusion: Employees reporting good work-life balance demonstrated 28 percent higher productivity scores and 35 percent lower turnover intentions. Flexible working arrangements and supportive organizational culture emerged as key enablers. Contribution: Research provides evidence-based recommendations for Indonesian service organizations to enhance productivity through improved work-life balance policies.